EXPRESSIONS OF THE GENTLE, ELEGANT, AND HOSPITABLE STYLE OF DALAT PEOPLE - Vu, Mong Doa (Trường Đại học Đà Lạt, 2024)
This study aims to analyze expressions of the gentle, elegant, and hospitable style of Dalat people and to clarify the differences and relationships between demographic factors and assessments of style. The research methods in this study include a survey of 1246 residents and travelers, 12 interviews, and 2 focus group discussions. The results show that a gentle style is the most prominent characteristic of Dalat people. The results also show that where people live before coming to Dalat and their length of time in Dalat influence their assessment of the style of Dalat people. Additionally, the study revealed that gender and education level influence evaluations of the style of Dalat people.